136k views
3 votes
Solve 2x^2 − 8x = −7

User GiH
by
4.9k points

1 Answer

3 votes

Answer:

The answer to your question is below

Explanation:

2x² - 8x = - 7

Divide by 2


(2)/(2) x^(2)  - (8)/(2) x    = (-7)/(2)

Complete the trinomial


x^(2)  - 4x + (2)^(2)  = (-7)/(2) + (2)^(2)

Simplify


x^(2)  - 4x  + (2)^(2)  = (- 7 + 4)/(2)


x^(2)  - 4x + 4 = (-3)/(2)

Factor

(x - 2)² =
(-3)/(2)

Get the square root


\sqrt{(x - 2)^(2)} = \sqrt{(-3)/(2)}

Simplification

x - 2 =±
\sqrt{(3)/(2)} i

x₁ = 2 +
\sqrt{(3)/(2)} i

x₂ = 2 -
\sqrt{(3)/(2)}